Computed Tomography-Galactography Virtual Endoscopy: A Better Imaging Method for the Diagnosis of Pathologic Nipple Discharge - Nan Ma; Jiang Zhu; Yawen Wang; Kai Zhang; Song Zhao; Yongfeng Liang; Yan Deng; Rong Ma (IMR Press, 2023)
Background: The preoperative diagnosis of pathologic nipple discharge (PND) in clinical settings remains challenging. Computed tomography-galactography virtual endoscopy (CT-G VE) was used for the intracavity imaging of discharging lactiferous ducts in a three-dimensional space, and the diagnostic performance of CT-G VE was compared with that of ultrasonography and galactography. Methods: This study included 41 patients with single-orifice PND who underwent ultrasonography, galactography, and CT-G VE before surgery. The postoperative histopathologic results were regarded as the gold standard for diagnosis. Qualitative data were analyzed using Fisher's precision probability test. Receiver operating characteristic (ROC) curve analysis was performed for ultrasonography, galactography, and CT-G VE to evaluate their diagnostic performances for the detection of PND diseases. Results: CT-G VE provided clear intracavity images of the discharging lactiferous ducts. The results of CT-G VE could be divided into five categories: negative, polypoid-solitary, polypoid-multiple, combined, and superficial types. The types were related to the histopathologic results. The detection ability of CT-G VE for high-risk and malignant lesions was higher than that of ultrasonography (p = 0.0056) and galactography (p = 0.0008). The detection abilities of CT-G VE alone and CT-G VE combined with ultrasonography were comparable. The cut-off point for CT-G VE was the polypoid-solitary type. The average effective dose for a single patient undergoing both chest CT and CT-G VE at the same time was 1.66 ± 0.78 msV. Conclusions: The diagnostic performance of CT-G VE was better than that of ultrasonography and galactography in detecting high-risk and malignant lesions of PND. This study proposed a grading system to aid decision-making and communication between clinicians in clinical practice.